1981
DOI: 10.1007/bf01795750
|View full text |Cite
|
Sign up to set email alerts
|

Cyanamide mediated syntheses of peptides containing histidine and hydrophobic amino acids

Abstract: Using the model of a primitive earth evaporation pond, the synthesis of three histidyl peptides in yields up to 11% was demonstrated when aqueous solutions of histidine, leucine, ATP, cyanamide, and MgCl2 were evaporated and heated for 24 h at 80 degrees C. In addition, peptides were formed in yields of up to 56%, 35%, and 21%, respectively for phenylalanine, leucine, and alanine when aqueous solutions of the appropriate amino acid were evaporated and heated with cyanamide and one or more of the following comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Clays and other fine grained sedimentary minerals may have provided the most likely surface for adsorption and condensation of amino acids owing to their high specific surface area (Ponnamperuma et al, 1982;Porter et al, 1998). Although many previous studies have examined the effects of minerals on peptide elongation in evaporative environments (Fox and Harada, 1958;Dose, 1983;Rode et al, 1999;Plankensteiner et al, 2004), as well in the presence of various condensing agents (Chang et al, 1969;Hawker and Oró , 1981;Hill et al, 1998;Liu and Orgel, 1998a,b;Leman et al, 2004), few studies have examined the catalytic effects of mineral surfaces on unactivated aqueous peptide oligomerization or degradation.…”
Section: Introductionmentioning
confidence: 96%
“…Clays and other fine grained sedimentary minerals may have provided the most likely surface for adsorption and condensation of amino acids owing to their high specific surface area (Ponnamperuma et al, 1982;Porter et al, 1998). Although many previous studies have examined the effects of minerals on peptide elongation in evaporative environments (Fox and Harada, 1958;Dose, 1983;Rode et al, 1999;Plankensteiner et al, 2004), as well in the presence of various condensing agents (Chang et al, 1969;Hawker and Oró , 1981;Hill et al, 1998;Liu and Orgel, 1998a,b;Leman et al, 2004), few studies have examined the catalytic effects of mineral surfaces on unactivated aqueous peptide oligomerization or degradation.…”
Section: Introductionmentioning
confidence: 96%
“…The prebiotic formation of peptides/proteins, being very basic molecules for the evolution of living organisms, has been subject of numerous experiments and discussions, mostly based on the assumption of large amounts of condensation reagents on the primitive earth, even as cyanamides, ATP, inorganic polyphosphates and heterocyclic compounds (Hulshoff and Ponnamperuma, 1976;Hawker and Oro, 1981;Rishpon et al 1982;Rabinovitz and Hampai, 1985;Yamanaka et al, 1988). Other authors have shown that melting of amino acids within 120 and 200 °C also leads to condensation (Fox and Dose, 1977).…”
Section: Introductionmentioning
confidence: 98%
“…However, it seems more likely to us that the chemical evolution might have taken place in the primitive oceans as a more universal place where peptides were formed from amino acids with an aid of various condensing agents and were accumulated gradually against their hydrolysis under mild conditions. Several simulation experiments were performed from such a viewpoint in aqueous solutions containing condensing agents (Steinman et al, t964, 1966;Rabinowitz et al, 1969;Chung et al, 1971;Rabinowitz and Hampei, 1978;Hawker and Oro, 1981;Sakurai and Yanagawa, 1984;Yamanaka et al, 1988).…”
Section: Introductionmentioning
confidence: 99%